Synergism of enzymes and molecularly imprinted polymers in electrochemical sensors - Yarman, Aysu; Oktay, Aysel; Tarhan, Ismail Adnan; Sinsoysal, Esin; Scheller, Frieder W. (ELSEVIER, 2025)
Molecularly imprinted polymers (MIPs) have been established as effective specifiers in clinical diagnostics and environmental analysis for a large spectrum of analytes spanning from low-molecular-weight substances to proteins, including enzymes. The synergism of MIP technology and enzyme technique is mirrored on the one hand by the high affinity, which results in an excellent analytical performance for the determination of enzymes by MIP-sensors, and on the other hand, in the improvement of preparation and readout of MIPs by using enzymes as tools. In addition, the creation of catalytically active MIP has been derived from the transition state concept of enzymatic substrate conversion. The integration of MIPs for enzymes in electrochemical sensors offers distinct benefits, e.g., the direct readout of the catalytic activity or the direct electron transfer with redox-active groups ensures excellent specificity. On the other hand, enzymes simplify the MIPs synthesis and improve the signal processing of electrochemical sensors.
Keywords: Molecularly imprinted polymer; Enzymes; Biomimetic sensors; Electrochemical readout; HORSERADISH-PEROXIDASE; RECOGNITION; BIOSENSOR; MIMICS; ANTIBODIES; PEPTIDES; Chemistry